Trends in research on relationship between root exudates and soil phosphorus: a bibliometric analysis - Ding, Yijie; Yao, Jiabao; Li, Fengqing; Chen, Shiyou; Wang, Hui; Hou, Lingyu; Liu, Lei; Sun, Qiwu (Frontiers in Plant Science, 2025)
IntroductionPhosphorus (P) is an essential element for plant growth, but low availability of soil phosphorus limits agricultural and forestry development. Root exudates play a significant role in enhancing soil phosphorus availability.MethodsBased on bibliometric methods, this study conducted a quantitative analysis of 276 relevant articles from the Web of Science database between 2001 and 2024 using visualization tools such as CiteSpace and VOSviewer. The analysis explored multiple dimensions, including publication volume, contributing countries, highly cited literature, and keyword trends.ResultsThe results revealed that research in this field has gradually gained attention over the past two decades, with a rising trend in publications, particularly dominated by China. Studies primarily focused on botany, soil science, and agronomy, with frequent publications in journals such as Plant and Soil. Through clustering of high-frequency keywords related to root exudates and soil phosphorus interactions, research hotspots were found to have expanded from model plants and plant growth traits to diverse plant species and deeper mechanistic explorations.ConclusionFuture research should emphasize international collaboration, integrate controlled laboratory experiments with field trials, and leverage multidisciplinary approaches to advance practical applications, providing insights for addressing potential soil phosphorus crises and providing scientific support for the sustainable development of global agriculture and forestry and carbon neutrality goals.